Quantification of interfacial motions following primary and revision total knee arthroplasty: A verification study versus experimental data. Issue 1 (31st July 2017) - Conlisk, Noel; Howie, Colin R.; Pankaj, Pankaj
ABSTRACT: Motion at the bone–implant interface, following primary or revision knee arthroplasty, can be detrimental to the long‐term survival of the implant. This study employs experimentally verified computational models of the distal femur to characterize the relative motion at the bone–implant interface for three different implant types; a posterior stabilizing implant (PS), a total stabilizing implant (TS) with short stem (12 mm × 50 mm), and a total stabilizing implant (TS) with long offset stem (19 mm × 150 mm with a 4 mm lateral offset). Relative motion was investigated for both cemented and uncemented interface conditions. Monitoring relative motion about a single reference point, though useful for discerning global differences between implant types, was found to not be representative of the true pattern and distribution of motions which occur at the interface. The contribution of elastic deformation to apparent reference point motion varied based on implant type, with the PS and TSSS implanted femurs experiencing larger deformations (43 and 39 μm, respectively) than the TSLS implanted femur (22 μm). Furthermore, the pattern of applied loading was observed to greatly influence location and magnitude of peak motions, as well as the surface area under increased motion. Interestingly, the influence was not uniform across all implant types, with motions at the interface of long stemmed prosthesis found to be less susceptible to changes in pattern of loading. These findings have important implications for the optimization and testing of orthopedic implants in vitro and in silico. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:387–396, 2018.